2003
DOI: 10.1046/j.1439-0396.2003.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on the feeding habits of roe deer (Capreolus capreolus) in the western Alps

Abstract: Roe deer feeding habits were studied in the western Alps during the summer season using the faecal analysis method. The diet of cattle grazing in the same area was also investigated and the trophical niche overlap between the two species was determined. The roe deer diet was found very variable and mostly composed of dicotyledons, with Leguminosae and Cistaceae as prevalent species. Monocotyledons, mainly represented by Graminaceae, were consumed to a lesser extent. A significant preference was observed for Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…Thus, the heavy use of grasses may be related to the absence of other resources at high altitude. Percentages of graminoids in the diet up to 15-30% have been reported for the roe deer (Tixier & Duncan, 1996;Cornelis et al, 1999), and in our study area Mussa et al (2001) found 16-26% of graminoids.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, the heavy use of grasses may be related to the absence of other resources at high altitude. Percentages of graminoids in the diet up to 15-30% have been reported for the roe deer (Tixier & Duncan, 1996;Cornelis et al, 1999), and in our study area Mussa et al (2001) found 16-26% of graminoids.…”
Section: Discussionsupporting
confidence: 69%
“…However, only little is known about the ecology, including the feeding ecology, of roe deer in Mediterranean environments (Linnell et al 1998). Most studies on their diet refer to mountain areas where summer conditions are less severe (Grigorov 1976;Fandos et al 1987; Bartolomé et al 2002;Mussa et al 2003), whereas studies from the lower altitudes were based on small sample sizes (Fandos et al 1987) or on a newly introduced population (Guilhem et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have described patterns of diet overlap between wild and domestic ruminants to assess competitive interactions (e.g., Mysterud 2000;Pordomingo and Rucci 2000;Mussa et al 2003). A high level of overlap in resource exploitation was used to support the hypothesis of interspecific competition (Belovsky 1986, e.g., Breebaart et al 2002, which most likely occurs between introduced livestock and wildlife (Stewart et al 2002;Voeten and Prins 1999), while native sympatric species generally show low dietary overlap as a consequence of niche separation and resource partitioning (Hartnett et al 1997).…”
Section: Introductionmentioning
confidence: 99%